Projeto, construção e desenvolvimento metodológico de um aparelho de destilação. Estudo de caso: produção de etanol anidro via destilação extrativa utilizando glicerol - Jardim, Herbert Aires Sousa Pereira Magalhães (2014)
Ethanol is a renewable fuel produced from biomass. Starting in 1975, Brazil began a national program to promote ethanol production in large scale, the ProAlcool Programme. In the harvest 2012/13 it was produced 23.64 billion of litters of ethanol, from that 9.85 billion was in anhydrous form. The anhydrous ethanol is mainly used as a gasoline additive. This mix reduces the dependence on fossil fuels, improves the engine performance and reduces the emission of toxic gases. Anydrous ethanol can be produced by azeotropic distillation (cyclohexane), by extractive distillation (mono ethylene glycol) or by molecular sieves technology (zeolytes). The objective of this work was the construction and operation of a distillation apparatus (in a bench scale) with the purpose of evaluating the extractive distillation of hydroalcoholic solutions of ethanol employing glycerol as solvent, in substitution of mono ethylene glycol. The substitution is motivated by several factors indicated by the literature like the biodiesel production growth, whose glycerol is a byproduct; the low toxicity; the superior capacity to promote the relative volatility increase of water-ethanol solution; and the inferior energetic consumption. The column was composed by three glass modules with five perforated plates each module. On the top it was used a glass coil condenser. As reboiler it was used a two litters round bottom boiling flask linked to a heating mantle. The feed of ethanol, solvent (glycerol) and the bottom product withdraw was made with pumps. The distillation system was modelled and simulated in the Aspen Plus software using the RadFrac distillation model and NRTL (non-random two-liquid model) thermodynamic model. Four simulations were made for different ethanol feed compositions (25, 35 and 45 wt %). Three simulations were made without the glycerine feed and one with solvent feed and 35% ethanol feed. The distillation column was operated in total reflux with 0.599 L/h ethanol feed flow and 0.341L/h glycerine feed flow. The systems without the solvent reached a mass purity of ethanol of 94.1% in distillate (45% of ethanol feed). The process with the solvent reached a purity of 99.8% in distillate. The four simulated conditions were experimentally evaluated. The experimental results confirmed that the use of glycerine feed promoted an improvement in separation, reaching distillate purity over 99%. Experiments without the glycerine reached compositions around 90%. Murphree efficiencies were determined in all experiments carried out. For the systems without the solvent the obtained efficiencies were: 45% (25% ethanol feed), 30% (35% ethanol feed), 35% (45% ethanol feed). The system with glycerine feed reached 70% efficiency.